2013
DOI: 10.1016/j.jval.2013.08.187
|View full text |Cite
|
Sign up to set email alerts
|

An Economic Model to Compare Linezolid and Vancomycin for the Treatment of Confirmed Methicillin-Resistant Staphylococcus aureus Nosocomial Pneumonia in Germany

Abstract: Objectives: To evaluate economic impact of linezolid (LZD) versus vancomycin (VAN) for treatment of confirmed methicillin-resistant Staphylococcus aureus(MRSA) nosocomial pneumonia (NP) in German health care system. MethOds: A 4 week decision model was developed capturing 1 st and 2 nd line therapy. Published literature (primarily Wunderink 2012, reported 54.8% clinical efficacy for LZD vs. 44.9% for VAN in modified Intent-to-Treat population at End of Study for treatment of MRSA NP) and expert opinion provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…All but two [38,39] of the nine studies considered MRSA HAP/VAP: four found linezolid to be cost-effective [33,40,43,46]; and three found linezolid to be less costly and more effective [25,34,45]. These conclusions for treating MRSA HAP accord with those reached by Zhang et al [49], who include vancomycin and linezolid amongst a number of comparators.…”
Section: Modelling Results Reported By Studiesmentioning
confidence: 65%
See 4 more Smart Citations
“…All but two [38,39] of the nine studies considered MRSA HAP/VAP: four found linezolid to be cost-effective [33,40,43,46]; and three found linezolid to be less costly and more effective [25,34,45]. These conclusions for treating MRSA HAP accord with those reached by Zhang et al [49], who include vancomycin and linezolid amongst a number of comparators.…”
Section: Modelling Results Reported By Studiesmentioning
confidence: 65%
“…Linezolid and vancomycin are only active against Gram-positive infections and five studies focused solely on cases where these organisms were confirmed [25,34,43,45,46]; four studies drew on clinical trials where patients received aztreonam for Gram-negative coverage, but either did not consider its costs in their model [38][39][40] or excluded patients with Gram-negative infections [33].…”
Section: Modelling Results Reported By Studiesmentioning
confidence: 99%
See 3 more Smart Citations